2020
DOI: 10.1002/advs.202000258
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive, Reliable, and High‐Temperature‐Resistant Flexible Pressure Sensor Based on Ceramic Nanofibers

Abstract: Flexible pressure sensors are essential components for soft electronics by providing physiological monitoring capability for wearables and tactile perceptions for soft robotics. Flexible pressure sensors with reliable performance are highly desired yet challenging to construct to meet the requirements of practical applications in daily activities and even harsh environments, such as high temperatures. This work describes a highly sensitive and reliable capacitive pressure sensor based on flexible ceramic nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 34 publications
2
81
1
Order By: Relevance
“…They usually have better stretchability, better softness, better compatibility, and higher sensitivity and have been richly developed in recent years. [359][360][361][362] In addition to capacitive and resistive types that can also be used to measure strain, commonly used ones also include piezoresistive and triboelectric types. [360] The mechanisms are shown in order in Figure 14g.…”
Section: Interactive Perception Sensorsmentioning
confidence: 99%
“…They usually have better stretchability, better softness, better compatibility, and higher sensitivity and have been richly developed in recent years. [359][360][361][362] In addition to capacitive and resistive types that can also be used to measure strain, commonly used ones also include piezoresistive and triboelectric types. [360] The mechanisms are shown in order in Figure 14g.…”
Section: Interactive Perception Sensorsmentioning
confidence: 99%
“…As-fabricated, the nanostructured capacitor features an air gap between pillars sandwiched between the upper and lower electrodes, so that both the overlapped area and distance, as well as the effective dielectric constant, are changed with applied pressure [42] . Beyond the traditional capacitive sensor, the ionic sensor based on ion-interfacial sensing has been widely investigated in recent years because of its unique double electrode layer structure [43][44][45] . For instance, Bai et al [44] reported an ionic sensor based on a graded intrafillable architecture with a high sensitivity (> 220 kPa -1 ) in an ultra-broad sensing range (0.08 Pa-360 kPa).…”
Section: Capacitive Mechanismmentioning
confidence: 99%
“…The ceramic nanofibers have been extensively studied for gas sensing applications due to their advantages such as good directional carrier transport, high surface energy, large surface-to-volume ratio, high chemical stability, great sensing performance. Ceramics are inherently resistant to aggressive physical and corrosive chemical circumstances and they offer significantly minimized hysteresis with increased relaxation time, which improves the stability, performance, and response time of pressure sensors [87]. Many researchers showed the applicability of electrospun ceramic nanofibers in gas sensing applications for detection of many different gases such as acetone [34,49,[88][89][90][91][92][93][94][95][96][97], ethanol [98][99][100][101], formaldehyde [102], ammonia [103][104][105][106][107], hydrogen sulfide [108], nitrogen dioxide [109][110][111], acetic acid [112], carbon monoxide [113,114], hydrogen [115], and toluene [116].…”
Section: Gas Sensorsmentioning
confidence: 99%
“…CNFs were also utilized in development of highly sensitive and reliable capacitive pressure sensors. Using flexible TiO 2 ceramic nanofibrous networks, Fu et al [87] developed a capacitive pressure sensor and studied the capacitance-to-pressure Recent Advances in Applications of Ceramic Nanofibers DOI: http://dx.doi.org/10.5772/intechopen.97118…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation